Políticas públicas y agricultura familiar en América Latina ante los escenarios agroalimentarios - Patrouilleau, María Mercedes (2025)
The construction of narrative scenarios is a key analytical strategy for policy analysis, as it provides a vision of the future and opens up the field of action to address complex problems that require strategic and comprehensive approaches. In this study, four agrifood scenarios for Latin America and the Caribbean have been developed as part of a team effort by the PP-AL Network. The scenarios were used analytically to question the future of policies for family farming in the region. The scenarios were constructed using the following techniques: horizon scanning, analysis of key factors and morphological analysis. The policy challenges posed by the scenarios were then contrasted with the state of the art of family farming policies. The results include: the analysis of thirty key factors, four agrifood scenarios with their implications for the family farming sector and the challenges of public policies at different levels, with a time horizon to 2040.